Exploring COVID-19 Vaccine Hesitancy and associated factors among Medical College Students - Ahmad, Nasir; Zakriya, Muhammad; Shah, Zulkifal (ADVANCES IN BASIC MEDICAL SCIENCES, 2025)
OBJECTIVE: This study aimed to assess the frequency of COVID-19 vaccine hesitancy among medical college students. In response to the COVID-19 pandemic, the scientific and regulatory communities swiftly developed and approved vaccines to combat the highly contagious SARS-CoV-2 virus. However, the expedited processes to address the public health crisis led to limited time for thorough safety testing of these vaccines, resulting in doubts among the general, academic, health professionals, and scientific communities. Additionally, reports of side effects more severe than the disease itself have contributed to vaccine hesitancy among the public. Given their role in disseminating accurate information and administering vaccinations, understanding medical science students’ vaccine hesitancy is essential to the COVID-19 response. METHODS: A cross-sectional survey using online forms observed the level of COVID-19 vaccine hesitancy in 299 medical college students of both genders from January 20 to February 20, 2023. The study was conducted at Jinnah Medical College after ethical approval was obtained from the institutional ethical review board. RESULTS: A total of 299 (65.2% male and 34.8% female) medical students (MBBS) participated in the study. Most of the students, 274 (91.6%) marked themselves as vaccinated, whereas 25 (8.4%) were not vaccinated. A series of questions was asked to determine the causes of hesitancy. Despite the 91.6% vaccination rate, the initial vaccine acceptance rate was 71.9% among the participants. Most of the initially hesitant students changed their minds and got vaccinated. The side effects observed ranged from 28.6 to 45.1%, and no prominent impact of psychological factors was observed on the side effects. CONCLUSION: The vaccine acceptance and vaccination rates were high among the students. About half of the students observed side effects that were not correlated with the psychological impact of COVID-19.